ESTIMATIVAS DE VARIÁVEIS PARA PLANEJAMENTO DA COMPOSIÇÃO DE PLANTIOS NA FLORESTA URBANA - Mata, Jéssica Batista da (2019)
Studies on how urban forest grows are important to generate information for the agencies responsible for its management, to assist its effective maintenance, to promote the provision of benefits, and the reduction of costs. This research had as objective to analyze the growth patterns of Handroanthus heptaphyllus (Vell.) Mattos and Platanus x acerifolia (Aiton) Willd. present in the urban forest of Irati, Parana state. In this sense, we verified the allometric relationships, crown area and volume, and growth estimates over the years. We evaluated the crown area projection in the horizontal direction employing eight crown rays to estimate it and compared it with the crown area determined through four and two rays, to indicate the most practical and efficient way for this. By the vectorization of tree crown images, we estimated the area of vertical crown projection and compared it with the estimates made by equations of geometric figures (rectangle, ellipse, circle, triangle, and parabola), to indicate which method would be easily determined from inventory data. To verify the three-dimensional shape of trees' crowns, we determined the hypothetical crown volume by geometric figures (parallelepiped, ellipsoid, sphere, cone, and paraboloid). We used different models to estimate the dimensions of the crown as a function of diameter at breast height (DBH in cm) and/or total height (m). We used partial trunk analysis to study the growth of the trees, and the data were used in the biological model of Chapman-Richards to understand the trunk and crown diameter growth over the years. We observed that two canopy rays are efficient to estimate the vertical projection of the crown area since they are correctly selected one on the north - east face and one on the south - west face. The triangle figure was the one that best represented the crown of the two species, so the cone was the best figure to calculate the crown volume. The canopy diameter can be estimated using the DBH, although the height variable can improve the model fit. The Chapman-Richards model was efficient to estimate the DBH over the years for both species panted in urban areas, especially at more advanced ages. This information allows us to help the management process of urban forest composition because it can generate growth trends and the degree of local occupation over the years in urbanized areas.